Genomic characterization of carbapenem-non-susceptible Pseudomonas aeruginosa in Singapore - Jocelyn Qi-Min Teo; Cheng Yee Tang; Jie Chong Lim; Shannon Jing-Yi Lee; Si Hui Tan; Tse-Hsien Koh; James Heng-Chiak Sim; Thuan-Tong Tan; Andrea Lay-Hoon Kwa; Rick Twee-Hee Ong (Emerging Microbes and Infections)
Pseudomonas aeruginosa is a clinically important pathogen implicated in many hospital-acquired infections. Its propensity to acquire broad-spectrum resistance has earned the organism its status as a severe public health threat requiring urgent control measures. While whole-genome sequencing-based genomic surveillance provides a means to track antimicrobial resistance, its use in molecular epidemiological surveys of P. aeruginosa remains limited, especially in the Southeast Asian region. We sequenced the whole genomes of 222 carbapenem-non-susceptible P. aeruginosa (CNPA) isolates collected in 2006–2020 at the largest public acute care hospital in Singapore. Antimicrobial susceptibilities were determined using broth microdilution. Clonal relatedness, multi-locus sequence types, and antimicrobial resistance determinants (acquired and chromosomal) were determined. In this study, CNPA exhibited broad-spectrum resistance (87.8% multi-drug resistance), retaining susceptibility only to polymyxin B (95.0%) and amikacin (55.0%). Carbapenemases were detected in 51.4% of the isolates, where IMP and NDM metallo-β-lactamases were the most frequent. Carbapenem resistance was also likely associated with OprD alterations or efflux mechanisms (ArmZ/NalD mutations), which occurred in strains with or without carbapenemases. The population of CNPA in the hospital was diverse; the 222 isolates grouped into 68 sequence types (ST), which included various high-risk clones. We detected an emerging clone, the NDM-1-producing ST308, in addition to the global high-risk ST235 clone which was the predominant clone in our population. Our results thus provide a “snapshot” of the circulating lineages of CNPA locally and the prevailing genetic mechanisms contributing to carbapenem resistance. This database also serves as the baseline for future prospective surveillance studies.